Belobrada penica Sylvia cantillans - Gračner, Jože (Acrocephalus, 1991)
Caught at Lake Cerknica on 27th April 1990
Keywords: belobrada penica; Birds; Cerkniško jezero; opazovanje; Ornithology; ornitologija; ptice; Slovenia; Slovenija; Sylvia cantillans